The Intracellular Domain of the Frazzled/DCC Receptor Is a Transcription Factor Required for Commissural Axon Guidance. - Neuhaus-Follini, A.; Bashaw, G.J. (Neuron, 2015)
In commissural neurons of Drosophila, the conserved Frazzled (Fra)/Deleted in Colorectal Cancer (DCC) receptor promotes midline axon crossing by signaling locally in response to Netrin and by inducing transcription of commissureless (comm), an antagonist of Slit-Roundabout midline repulsion, through an unknown mechanism. Here, we show that Fra is cleaved to release its intracellular domain (ICD), which shuttles between the cytoplasm and the nucleus, where it functions as a transcriptional activator. Rescue and gain-of-function experiments demonstrate that the Fra ICD is sufficient to regulate comm expression and that both ?-secretase proteolysis of Fra and Fra's function as a transcriptional activator are required for its ability to regulate comm in vivo. Our data uncover an unexpected role for the Fra ICD as a transcription factor whose activity regulates the responsiveness of commissural axons at the midline and raise the possibility that nuclear signaling may be a common output of axon guidance receptors.